Effect of UV Irradiation on The Structure and Optical Properties of PVA/Cucl2 - Ahmed, Moustafa Tawfik (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The morphology and optical properties of doped PVA with Copper Chloride, CuCl2 have been investigated. The morphology of doped samples has been examined using both atomic force microscope (AFM) and scanning electron microscope (SEM) to investigate the effect of CuCl2 on the structure of PVA. X-ray diffraction showed that the crystallinity of PVA is increased with increasing CuCl2 ratio. In addition, FTIR spectra showed that, some absorbance bands such as bands of OH groups have been affected due to CuCl2 ratio and UV irradiation. On the other hand, the effect of CuCl2 ratio and UV irradiation on UV spectra of all samples has been carried out in the range from 200 to 800 nm. It is observed that, PVA is characterized by two absorbance bands at 278 and 313 nm. The values of absorbance edge, Urbach energy and the direct energy gap of all samples have been calculated.